2015
DOI: 10.1007/s10461-015-1144-5
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and HIV Testing in a National Sample of Women

Abstract: The HIV/AIDS epidemic continues to disproportionately affect racial and ethnic minority groups and women in the United States. Prevention research suggests that reduced alcohol use and increased HIV testing are associated with lower incidence of HIV transmission among high-risk populations. Multivariable logistic regression analyses of the 2009 National Health Interview Survey (NHIS) data were performed for a national sample of 15,470 adult women to examine the relationship between alcohol use and likelihood o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…28 In studies of younger individuals at-risk for HIV, excessive drinking was associated with increased risk behavior and lower overall health, including lower uptake of preventative services like regular HIV testing. 29,30 Our study findings suggest that this behavior has similar effects on HTC uptake across different age groups.…”
Section: Discussionsupporting
confidence: 53%
“…28 In studies of younger individuals at-risk for HIV, excessive drinking was associated with increased risk behavior and lower overall health, including lower uptake of preventative services like regular HIV testing. 29,30 Our study findings suggest that this behavior has similar effects on HTC uptake across different age groups.…”
Section: Discussionsupporting
confidence: 53%
“…A key contribution of this research is its use of the socioecological framework to systematically examine the role of alcohol use as a risk factor for HIV acquisition and transmission. While other studies have examined alcohol use and HIV testing among women [ 98 ], to the best of our knowledge, this is among the first studies to qualitatively examine perceptions of alcohol use as a risk factor for HIV acquisition and transmission for Black and African American women residing in urban and suburban communities. We explored this important question while also concurrently assessing HIV-related knowledge and HIV testing decision-making because protective factors such as HIV knowledge and HIV testing are central to mitigating HIV risk behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…57 Despite enhancing the risk of transmission by greater than 200%, research has consistently found a negative relationship between levels of drinking and the likelihood of ever testing for HIV. [58][59][60][61] For people who may have been exposed to HIV, knowledge is critical to making informed decisions. An antibody test is a serious event with potentially serious outcomes.…”
Section: Discussionmentioning
confidence: 99%